Analisis Kemampuan Pemahaman Siswa Pada Pembelajaran IPA Sistem Pernapasan Manusia Di Kelas V SDN 13 Pesing - Armet, Ambrosius; Rahmawati, Puji (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2026)
The purpose of this study was to determine the use of used bottle media in science learning, the types of learning media used, the obstacles faced by teachers and efforts to overcome obstacles in the use of media in science learning at SDN 13 Pesing. This type of research is phenomenological research with a qualitative descriptive method approach. The subjects of this study were fifth grade students. Data collection in this study used observation, interview, and documentation techniques. Data analysis techniques include three stages, namely data reduction, data presentation and conclusion stages. The results of the study stated the form of difficulty in understanding science subjects is that students have difficulty understanding when doing exercises, do not understand symbols; understand concepts and materials, factors causing difficulty in understanding the ability to classify respiratory system material are internal factors such as learning concentration does not last long, some students' memory abilities are low, students have difficulty understanding the meaning of the questions. External factors such as teachers providing understanding too quickly, not using media and students who often talk when the teacher explains efforts to overcome difficulties in understanding abilities are holding tutoring, holding remedial for those with low scores, changing the methods used, providing motivation and advice, using media that is appropriate to the material.